Participação do sistema purinérgico no locus coeruleus (LC) no controle cardiorrespiratório e térmico em normocapnia e hipercapnia em ratos não anestesiados - Biancardi, Vivian (Universidade Federal de São Carlos, 2011)
Locus coeruleus (LC) is considered as a chemosensitive region to CO2/pH in mammals and amphibians, mainly its noradrenergic neurons. The LC purinergic neuromodulation is of particular interest since adenosine 5′-triphosphate (ATP) acts as a neuromodulator in many brainstem areas involved in cardiovascular and respiratory regulation, which includes Locus coeruleus (LC). ATP acting on LC P2 receptors influences the release of noradrenaline (NE) and the LC noradrenergic neurons are involved in the CO2-drive to breathing. Thus, the goal of the present study was to investigate the role of purinergic neuromodulation in the LC in the ventilatory, thermal and cardiovascular responses during normocapnia and hypercapnia in Wistar male unanesthetized rats. We assessed the purinergic modulation of cardiorespiratory and thermal responses by microinjecting ATP P2X receptor agonist (α,β-MeATP, 0.5 nmoL/40 nL and 1 nmoL/40 nL) and P2 receptor non selective antagonists (PPADS 0.5 nmoL/40 nL and 1 nmoL/40 nL; suramin, 1 nmoL/40 nL) into the LC. Pulmonary ventilation (VE, plethysmography), mean arterial pressure (MAP), heart rate (HR) and body core temperature (Tb, dataloggers) were measured before and after unilateral microinjection (40 nL) of α,β-MeATP, PPADS, suramin or 0.9% saline (vehicle) into the LC during 60 min normocapnia or 30 min period of 7% CO2 exposure followed by 30 min of normocapnia. Under normocapnic conditions, α,β-MeATP did not affect any parameter, whereas PPADS decreased respiratory frequency (f), increased MAP and HR and suramin increased Tb, MAP and HR and did not change ventilation. Hypercapnia induced an increase in ventilation, a fall in HR and did not change Tb in all groups. During hypercapnia, α,β-MeATP produced a further increase in ventilation and did not cause changes in cardiovascular and thermal parameters, PPADS caused an increase in MAP, did not alter ventilation and Tb and suramin elicited increases in ventilation, MAP and bradycardia and did not change Tb. Thus, our data suggest that purinergic neuromodulation in the LC plays an important role in the cardiorespiratory control during hypercapnia and modulates cardiorrespiratory and thermal control during normocapnic conditions in unanesthetized animals.
Keywords: Respiração; Adenosina trifosfato; Suramin; PPADS; CO2; Neurofisiologia; Adenosina 5′-trifosfato (ATP); α,β-Metileno ATP; Receptores purinérgicos P2; Controle cardiovascular; Locus coeruleus (LC); Adenosine 5′-triphosphate (ATP); α,β-Methylene ATP; P2 purinergic receptors; Breathing; CIENCIAS BIOLOGICAS::FISIOLOGIA::FISIOLOGIA DE ORGAOS E SISTEMAS::FISIOLOGIA DA RESPIRACAO